SETTING AND COMMUNICATING OBJECTIVES IN BASKETBALL VERSUS BUSINESS ORGANIZATIONS - BRANGA, Vlad-Alexandru (Studia Universitatis Babeș-Bolyai Negotia, 2023)
Basketball and business organizations can be compared from various standpoints (organizational structure, type of teams, processes etc.). One such standpoint is regarding objective setting. By undergoing a literature review analysis on the topic of objective setting in basketball versus business organization, the author tried to answer the research question: “are there any differences in the way basketball and business organizations conduct their objective setting activities?” Considering this, the objective of this paper is to provide an insight into how objectives in basketball and business organizations are set, and if there are any similarities or differences in the way they conduct this activity. The results however, did not provide clear and sufficient information if there are any differences between how objectives are set and communicated in basketball versus business organizations. Furthermore, a simple literature review like this one cannot provide a clear answer to the research question, as the necessary information regarding objective setting in basketball organizations is, in most cases, not public or easily identifiable. Moreover, the author was not able to identify research on the topic of how exactly basketball organizations set their objectives or what criteria they take into consideration when setting these objectives. This proves the fact that topics like how basketball organization set their objectives for each season or what criteria they take into consideration when undergoing this activity could be considered relevant for a future and more detailed qualitative/ quantitative research having as target group: basketball teams that play in the Euroleague/Romanian National Basketball League. Article history: Received: June 5, 2023; Reviewed: August 31, 2023; Accepted: September 22, 2023; Available online: September 30, 2023; Available print: September 30, 2023. JEL classification: M12, M19